Pedagogical Content Knowledge in Organic Chemistry: A Case Study of the University Teacher - Parga-Lozano, Diana Lineth (2017)
From Science Education, the Pedagogical Content Knowledge (PCK) is making an important contribution to the analysis of teacher training and the improvement of professionals. As such, a study was conducted to characterise the PCK of a teacher holding a degree in chemistry teaching; he teaches organic chemistry concepts at a higher education institution. The research involved a case study and was qualitative in nature; document analysis was also used as an analytical technique; besides, information was collected by use of Representations of Content (ReCo), Pedagogical and Professional Experience Repertoires (PaP-eR), document analysis of the participating teacher’s work, classroom observation, and interviews. With these tools, we were able to determine the strengths and weaknesses of the participating teacher, and from there, to infer aspects that needed improving in training undergraduates in chemistry. I found that, in this case, the teacher sees himself as chemist and not as chemistry teacher (i.e. there is a lack of professional identity); perhaps, because it is the dominant factor in his disciplinary knowledge at the expense of topics related to the knowledge of school context, as well as historical-epistemological and psycho-pedagogical knowledge. The latter indicates, as a characteristic of the participant’s PCK, that this PCK is incipient due to the disarticulation of its components, which weakens the teaching of organic chemistry concepts. This suggests the need to strengthen the initial training of teachers in their role as teaching professionals, and to integrate components of the PCK.